2017
DOI: 10.3390/polym9030086
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Dimethyl-Substituted Polyviologen and Control of Charge Transport in Electrodes for High-Resolution Electrochromic Displays

Abstract: Electrochromic (EC) polymers such as polyviologens have been attracting considerable attention as wet-processable electrodes for EC displays, thanks to their brilliant color change accompanied with reversible redox reactions. To establish wider usage, achieving multicolor and high-resolution characteristics is indispensable. In this paper, we demonstrated that the introduction of substituents such as methyl groups into bipyridine units changed the stereostructure of the cation radicals, and thus shifted the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Especially, four polymer films have excellent electrochromic properties in the NIR region, which was characterized by high Δ T % values, fast response speed, high CE values and high stability performance, which make four polymers to be promising candidates for NIR device fabrications. Furthermore, all of the polymers could perform the color switches among the primary colors, which also provide the possibilities for the application of these polymers in the field of non-emitting display devices [ 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Especially, four polymer films have excellent electrochromic properties in the NIR region, which was characterized by high Δ T % values, fast response speed, high CE values and high stability performance, which make four polymers to be promising candidates for NIR device fabrications. Furthermore, all of the polymers could perform the color switches among the primary colors, which also provide the possibilities for the application of these polymers in the field of non-emitting display devices [ 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to the research of Hiroyuki Nishide, Kenichi Oyaizu, and coauthors, 395 charge transfer through the electrode substrate was the predominant route of electrical signal diffusion. Because each electrode was in direct contact with multiple EC pixels, the weaker surrounding charge transfer may also lead to the response (color change) of EC materials, although the charge transfer was fastest in the two facing electrodes due to the reduced electrical resistance (ohmic drop) and/or faster ion transport originating from the nearest distance.…”
Section: Passive Matrix and Signal Crosstalkmentioning
confidence: 99%
“…Apart fromelectropolymerization, a variety of polyviologens containing bromide or tosylate counter-ions have been synthesized via Menshutkin reactions of 4,4′-bipyridine and the corresponding alkyl halides or alkyl ditosylates [50,51,52,53,54,55]. In 2017, Sato et al reported the synthesis of dimethyl-substituted polyviologen with polyethylene glycol backbones by Menschutkin reaction (Figure 7) [56]. It was found that the introduction of methyl groups into the bipyridine scaffolds could alter the stereostructure and shift the color of the corresponding cation radicals from purple to blue.…”
Section: Viologen-based Electrochromesmentioning
confidence: 99%